The Impact of Economic Policy Uncertainty on Investment - Cash Flow Sensitivity: Does ESG Make Any Difference? - Sakti Ranjan Dash; Maheswar Sethi (Australasian Accounting, Business and Finance Journal, 2024)
This paper investigates the impact of Economic Policy Uncertainty (EPU) on Investment-Cash Flow Sensitivity (ICFS). Further, this study examines whether ESG moderates the impact of such uncertainty on the ICFS of the manufacturing firms in India. The study has applied system-GMM regression with a sample of 222 firms from 2012 to 2022. It reveals that EPU dampens corporate investment and magnifies the role of cash flow in corporate investment. Further, firms' Environmental, Social and Governance (ESG) performance decelerates the adverse impact of EPU on ICFS and makes the investment-cash flow less sensitive. Furthermore, the study highlights that ESG helps to access external funds easily. Overall, this paper contributes new insights to the present literature, and the outcomes of this study are of greater interest to economists, firms, managers, and investors.
Keywords: Macroeconomic Risk; EPU; Investment-Cash Flow Sensitivity; Manufacturing Firms; ESG